2020
DOI: 10.1109/tia.2020.2990887
|View full text |Cite
|
Sign up to set email alerts
|

ALADIN-Based Coordinated Operation of Power Distribution and Traffic Networks With Electric Vehicles

Abstract: Electric vehicles (EVs) are recognized as a promising remedy for the environmental crisis and fuel shortage faced by modern metropolises. But meanwhile, with the popularization of EVs, the unordered charging of EVs will have negative impacts on both the power distribution network (DN) and the traffic network (TN). The well scheduled EV charging/discharging behaviors could participate in the coordinated operation of TN and DN to significantly enhance the energy utilization efficiency of both networks. With an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Moreover, the values V ac , V dc ,I ac ,I dc and P total can be determined in term of power factor (x 1 ) by placing the values of a and b from Equation (10) and their representation is given in Equations ( 12) to (16).…”
Section: Working Principle Of the Proposed Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the values V ac , V dc ,I ac ,I dc and P total can be determined in term of power factor (x 1 ) by placing the values of a and b from Equation (10) and their representation is given in Equations ( 12) to (16).…”
Section: Working Principle Of the Proposed Systemmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] These studies [6][7][8][9][10][11][12] have focused on the impact of EV charging power demands on the power quality of the distribution network, such as determining system losses, voltage drops, network congestion, under-voltage and overcurrent events, and phase imbalances. Previous [13][14][15][16][17] studies investigated the impact of EV charging power demands on voltage profiles; these found that a large additional demand due to high penetration of EVs could result in voltage drop problems, such as violation of the voltage limit and voltage unbalance. Further, the power energy research community has explored the optimal placement of the charging station to mitigate the challenges associated with grid stability.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al,in [27], modeled the interaction between the energy-constrained devices and unmanned aerial vehicles and presented the multiple-stage dynamic bipartite matching strategy in IoT. Sun et al, in [28], studied how to improve the energy utilization efficiency, through coordinating the traffic network and power distribution network. Ferdowsi et al, in [29], designed the safe controller to protect the autonomous connected vehicles' network being attacked physically.…”
Section: Related Workmentioning
confidence: 99%
“…Break the loop. (27) end if (28) end for (29) end for (30) end for (31) Output: θ * i , while both p * re (t) and p * tr (t) can be achieved. and ω 2 .…”
Section: Simulationmentioning
confidence: 99%
“…A simplified charge-control algorithm for deterministic traffic networks was presented to ease computational complexity. Sun et al [20] proposed a traffic-distribution coordination mechanism to minimize the travel cost and energy service cost of each EV driver. An augmented Lagrangian alternating direction inexact Newton model was employed to coordinate operation of traffic and power distribution networks.…”
Section: Introductionmentioning
confidence: 99%